Photocuring dual-network sensing hydrogel material and preparation method thereof
By photocuring the dual network sensing hydrogel material, the non-toxic I2959 catalyst is used to catalyze the photoinitiator to generate free radicals under ultraviolet light, solving the problem of insufficient molding speed and compression performance of the existing hydrogel, achieving rapid molding and controlling the molding process, and improving mechanical properties and conductive capabilities.
Patent Information
- Application Number
- CN202510044991.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing flexible sensing hydrogels have shortcomings in molding speed and compression performance, and the tetramethylethylenediamine (TEMED) used during the molding process is a toxic substance, which is difficult to control the molding time.
Using photocured dual network sensing hydrogel material, the photoinitiator generates free radicals under ultraviolet light irradiation is used to achieve rapid molding and control of the molding process.
The rapid molding of hydrogels in a short time is achieved, which avoids environmental pollution, and can finely regulate the molding process by controlling the light time, improving the mechanical properties and conductive capabilities of the hydrogels.
Smart Images

Figure CN119798544A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of hydrogel sensing, and in particular to a photocurable double-network sensing hydrogel material and a preparation method thereof. Background Art
[0002] Hydrogels contain a large number of flexible polymer networks with hydrophilic groups such as hydroxyl, carboxyl and amino groups. They can absorb and retain a large amount of water in a liquid environment, but are almost insoluble in water. Flexible materials are used as the hydrogel substrate, and conductive materials are added to achieve conductive effects. When the hydrogel is subjected to different strains, the conductive material changes in the internal pathway, which is a strain sensing hydrogel. Piezoresistive sensors change their internal pathways by deformation to achieve different conductive effects, playing a very important role in the fields of medicine, food, engineering, etc. In recent years, the innovative development and research of flexible sensor devices have promoted their application in the field of smart packaging, and have had a more intelligent impact on human body sensing and food monitoring.
[0003] There are many ways to form hydrogels. Acrylamide-based hydrogels usually promote cross-linking of acrylamide and cross-linking agents by generating free radical groups through persulfate ions. It is usually necessary to add tetramethylethylenediamine (TEMED) to accelerate the decomposition of persulfide to produce free radicals. However, TEMED is a toxic substance. After the hydrogel is formed, it will emit an amine odor, which affects the application of the hydrogel. In addition, the molding system composed of persulfide and TEMED cannot control the hydrogel molding time. Therefore, it is of great research significance to use safe and non-toxic initiators to initiate hydrogel molding and control the molding process. Summary of the invention
[0004] The purpose of the present invention is to provide a photocurable dual-network sensing hydrogel material and a preparation method thereof, aiming to solve the problems of flexible sensing hydrogel in molding speed and compression performance. By using non-toxic I2959 catalyst, it can be molded in a shorter time while avoiding environmental pollution, and the control of the hydrogel molding process can be achieved by controlling the illumination time.
[0005] The present invention achieves the above-mentioned purpose through the following technical solutions: A photocurable dual network sensing hydrogel material and a preparation method thereof, using cellulose ether derivatives and acrylamide (AM) hydrogel precursors, adding a photoinitiator and a crosslinking agent, catalyzing the photoinitiator to generate free radicals under ultraviolet light irradiation to synthesize the hydrogel, comprising the following steps: (1) Preparation of double network precursor solution: The cellulose ether derivative is stirred evenly until it is completely dissolved, and then carboxylated cellulose nanofibers and acrylamide are added, and stirred evenly at a low speed to avoid generating bubbles, until a double network precursor solution is formed; (2) Preparation of hydrogel: After the components in (1) are completely dissolved, add the photoinitiator I2959 and the cross-linking agent, add the conductive carbon material, stir evenly and immediately transfer to the mold, and irradiate under ultraviolet light for 5-10 minutes until it is formed, then transfer to the metal ion solution for immersion to enhance the mechanical properties of the hydrogel.
[0006] Preferably, the mass fraction of the cellulose ether derivative added in step (1) is 0.5wt%-2.5wt% relative to the water solvent, the mass fraction of the CCNF added is 5-10wt% relative to the water solvent, and the mass fraction of the acrylamide added is 5wt%-25wt% relative to the water solvent. The stirring is carried out at 25°C-28°C, the rotation speed is 50-200 rpm, and the stirring time is 6-24 h.
[0007] Preferably, the cellulose ether derivative is one of sodium carboxymethyl cellulose type I, hydroxyethyl cellulose and hydroxypropyl cellulose.
[0008] Preferably, the mass fraction of the photoinitiator added in step (2) is 0.1wt%-0.25wt% relative to the water solvent, the mass fraction of the added cross-linking agent is 0.025wt%-0.075wt% relative to the water solvent, and the volume fraction of the conductive carbon material added is 5%-25% relative to the volume of the water solvent. The stirring is carried out at 25°C-28°C, the rotation speed is 50-200 rpm, and the stirring time is 6-24 h.
[0009] Preferably, in step (2), the metal ion concentration is 0.1 mol / L-0.6 mol / L, the immersion is carried out at 25°C-28°C, and the immersion time is 6-24 h.
[0010] Preferably, the crosslinking agent added in step (2) is one of N,N'-methylenebisacrylamide, glutaraldehyde, and N-hydroxymethylacrylamide, and the conductive carbon material used is at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes, graphite powder, and carbon nanofibers.
[0011] Preferably, the ultraviolet light wavelength used in step (2) is 365-405 nm, the metal ion used is one of iron ion, zirconium ion, cerium ion and lead ion, and the irradiation time is 5-15 min.
[0012] The invention discloses a photocurable double network sensing hydrogel material and a preparation method thereof. The hydrogel obtained by the preparation method has excellent mechanical properties and a controllable molding process and can be quickly molded in a short time.
[0013] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention can achieve the regulation of hydrogel molding by forming under photocuring conditions, compared with the catalytic system of persulfate ions and tetramethylethylenediamine. At the same time, photocuring is helpful for the development of 3D printing.
[0014] (2) Compared with heat-induced hydrogels, the hydrogels of the present invention can be rapidly formed in a shorter time and formed evenly, thus avoiding gel forming defects caused by uneven heating.
[0015] (3) The metal ions used in the present invention can not only improve the mechanical properties of the hydrogel, but also act as a part of the conductive network to improve the conductivity of the double network hydrogel.
[0016] (4) The ultraviolet light initiator used in the hydrogel of the present invention is safe and environmentally friendly, which reduces the harmful substances that may be released during the material preparation process and reduces their harm to the human body or the environment.
[0017] (5) The double-network hydrogel of the present invention exhibits better mechanical properties, such as higher compressive strength, and provides a stable material basis for complex conductive sensing application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The improvement of hydrogel hardness by CMC addition; Figure 2 The improvement of the tensile properties of hydrogels by the amount of CCNF added; Figure 3 FeCl3 improves the mechanical properties of hydrogel; Figure 4 XRD patterns of hydrogels formed by each single factor; Figure 5 is the scanning electron microscopy image of the hydrogel; Figure 6 This is a real picture of the hydrogel. DETAILED DESCRIPTION
[0019] The present invention provides a photocurable dual network sensing hydrogel material and a preparation method thereof, comprising the following steps: (1) Preparation of double network precursor solution: Weigh 0.5 g of sodium carboxymethyl cellulose type I and 1.5 g of CCNF and dissolve them in 20 mL of deionized water, stir at 25 °C and 100 rpm until completely dissolved, then weigh 6 g of acrylamide and stir at 25 °C and 100 rpm until completely dissolved, avoiding the generation of bubbles, until a double network precursor solution is formed; (2) Preparation of hydrogel: After the components in (1) are completely dissolved, weigh 15 mg of N,N'-methylenebisacrylamide crosslinker, 30 mg of I2959 photoinitiator, a small amount of catalyst tetramethylethylenediamine 20 μL, and 4 mL of single-walled carbon nanotube dispersion, stir at 25°C 100 rpm for 30 min, and then transfer to the mold. Then irradiate under 405 nm ultraviolet light for five minutes to form the mold. The prepared hydrogel is immersed in 0.1 mol / L FeCl3 solution for 24 h to obtain a photocurable dual network sensing hydrogel.
[0020] The technical solution provided by the present invention is described in detail below in conjunction with the embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0021] (1) Performance regulation of double network hydrogels Example 1
[0022] At 25°C, 0.1 g of sodium carboxymethyl cellulose type I and 1.5 g of CCNF were weighed and dissolved in 20 mL of deionized water. The mixture was stirred at 25 °C and 100 rpm for 12 h until it was evenly and completely dissolved. 6 g of acrylamide, 15 mg of N,N'-methylenebisacrylamide crosslinker, 30 mg of I2959 photoinitiator, 20 μL of a small amount of catalyst tetramethylethylenediamine, and 4 mL of single-walled carbon nanotube dispersion were taken. The mixture was stirred evenly at 25 °C and 100 rpm until it was completely dissolved. After being transferred to a mold, it was irradiated under 405 nm ultraviolet light for five minutes to form a mold. The prepared hydrogel was immersed in 0.1 mol / L FeCl3 solution for 24 h. Example 2
[0023] At 25°C, 0.2 g of sodium carboxymethyl cellulose type I and 1.5 g of CCNF were weighed and dissolved in 20 mL of deionized water, and stirred at 25 °C and 100 rpm for 12 h until uniform and completely dissolved. 6 g of acrylamide, 15 mg of N,N'-methylenebisacrylamide crosslinker, 30 mg of I2959 photoinitiator, a small amount of catalyst tetramethylethylenediamine 20 μL, and 4 mL of single-walled carbon nanotube dispersion were taken, and stirred uniformly at 25 °C and 100 rpm until completely dissolved. After transferring to a mold, it was irradiated under 405 nm ultraviolet light for five minutes to form a mold. The prepared hydrogel was immersed in 0.1 mol / L FeCl3 solution for 24 h. Example 3
[0024] At 25°C, 0.3 g of sodium carboxymethyl cellulose type I and 1.5 g of CCNF were weighed and dissolved in 20 mL of deionized water. The mixture was stirred at 25 °C and 100 rpm for 12 h until it was evenly and completely dissolved. 6 g of acrylamide, 15 mg of N,N'-methylenebisacrylamide crosslinker, 30 mg of I2959 photoinitiator, 20 μL of a small amount of catalyst tetramethylethylenediamine and 4 mL of single-walled carbon nanotube dispersion were taken and stirred at 25 °C and 100 rpm until it was completely dissolved. After being transferred to a mold, it was irradiated under 405 nm ultraviolet light for five minutes to form a shape. The prepared hydrogel was immersed in 0.1 mol / L FeCl3 solution for 24 h. Example 4
[0025] At 25°C, 0.4 g of sodium carboxymethyl cellulose type I and 1.5 g of CCNF were weighed and dissolved in 20 mL of deionized water, and stirred at 25 °C and 100 rpm for 12 h until uniform and completely dissolved. 6 g of acrylamide, 15 mg of N,N'-methylenebisacrylamide crosslinker, 30 mg of I2959 photoinitiator, a small amount of catalyst tetramethylethylenediamine 20 μL, and 4 mL of single-walled carbon nanotube dispersion were taken, and stirred at 25 °C and 100 rpm until completely dissolved. After transferring to a mold, it was irradiated under 405 nm ultraviolet light for five minutes to form a mold. The prepared hydrogel was immersed in 0.1 mol / L FeCl3 solution for 24 h. Example 5
[0026] At 25°C, 0.5 g of sodium carboxymethyl cellulose type I and 1.5 g of CCNF were weighed and dissolved in 20 mL of deionized water, and stirred at 25 °C and 100 rpm for 12 h until uniform and completely dissolved. 6 g of acrylamide, 15 mg of N,N'-methylenebisacrylamide crosslinker, 30 mg of I2959 photoinitiator, a small amount of catalyst tetramethylethylenediamine 20 μL, and 4 mL of single-walled carbon nanotube dispersion were taken, and stirred at 25 °C and 100 rpm until completely dissolved. After transferring to a mold, it was irradiated under 405 nm ultraviolet light for five minutes to form a mold. The prepared hydrogel was immersed in 0.1 mol / L FeCl3 solution for 24 h. Example 6
[0027] At 25°C, weigh 0.6 g of sodium carboxymethyl cellulose type I, 1.5 g of CCNF, dissolve in 20 mLs of deionized water, stir at 25 °C 100 rpm for 12 h until uniform and completely dissolved, weigh 6 g of acrylamide, 15 mg of N, N'-methylenebisacrylamide crosslinker, 30 mg of I2959 photoinitiator, absorb a small amount of catalyst tetramethylethylenediamine 20 μL, 4 mL of single-walled carbon nanotube dispersion, stir at 25 °C 100 rpm until completely dissolved, transfer to the mold and irradiate under 405 nm ultraviolet light for five minutes to form, and soak the prepared hydrogel in 0.1 mol / L FeCl3 solution for 24 h. The hydrogel prepared in Examples 1-6 was tested for compression performance, with gel hardness as an indicator.
[0028] Testing of hydrogel properties: The hydrogel was compressed to 65% deformation using a texture analyzer (TMS-Pro), and the hardness of the hydrogel was recorded.
[0029] The specific test results are shown in Table 1 and Figure 1 CMC addition amount (g) Material hardness (N) Example 1 0.1g 100.54335 Example 2 0.2g 88.33059 Example 3 0.3g 85.28987 Example 4 0.4g 92.86676 Example 5 0.5g 99.29714 Example 6 0.6g 96.60535 Figure 1 The improvement of CMC addition on the hardness of hydrogel is Figure 1 It can be seen that 0.1g of CMC has almost no improvement on the hardness of acrylamide. A small amount of CMC is dispersed in the acrylamide network, and the hardness of the hydrogel is still mainly dominated by the acrylamide network. When AM is cross-linked, there is no other component blocking it under the action of the cross-linking agent, so the AM cross-linking is more sufficient and complete, and it has a more complete network. As the amount of CMC added increases to 0.3g, CMC is filled in the acrylamide network as a soft segment structure, which reduces the full contact between AM and the cross-linking agent and disperses the strong supporting effect of the acrylamide network. Therefore, the hardness of the acrylamide hydrogel is gradually reduced, and the hardness of the hydrogel reaches a minimum of about 85N. With the continued addition of CMC, the network structure of CMC gradually supports each other with the acrylamide structure, so the hardness gradually rises again and reaches the maximum hardness of the hydrogel at 0.5g. The prepared gel has better elasticity than pure AM hydrogel. When CMC continues to increase to 0.6g, due to the limited deionized water in the system, CMC A large number of bubbles are generated during the dissolution process. On the one hand, the bubbles will lead to incomplete cross-linking and the network structure of the hydrogel will not be uniform and complete. On the other hand, the presence of bubbles reduces the cross-linking density. Therefore, after the cross-linking is completed, it has a huge negative impact on the performance of the hydrogel and the hardness of the hydrogel is reduced again.
[0030] (2) Improvement of tensile properties by carboxylated cellulose nanofibers Example 1
[0031] At 25°C, 0.5 g of sodium carboxymethyl cellulose type I and 1.0 g of CCNF were weighed and dissolved in 20 mL of deionized water, and stirred at 25 °C and 100 rpm for 12 h until uniform and completely dissolved. 6 g of acrylamide, 15 mg of N,N'-methylenebisacrylamide crosslinker, 30 mg of I2959 photoinitiator, a small amount of catalyst tetramethylethylenediamine 20 μL, and 4 mL of single-walled carbon nanotube dispersion were taken, and stirred at 25 °C and 100 rpm until completely dissolved. After transferring to a mold, it was irradiated under 405 nm ultraviolet light for five minutes to form a mold. The prepared hydrogel was immersed in 0.1 mol / L FeCl3 solution for 24 h. Example 2
[0032] At 25°C, 0.5 g of sodium carboxymethyl cellulose type I and 1.25 g of CCNF were weighed and dissolved in 20 mL of deionized water. The mixture was stirred at 25 °C and 100 rpm for 12 h until it was evenly and completely dissolved. 6 g of acrylamide, 15 mg of N,N'-methylenebisacrylamide crosslinker, 30 mg of I2959 photoinitiator, 20 μL of a small amount of catalyst tetramethylethylenediamine and 4 mL of single-walled carbon nanotube dispersion were taken and stirred at 25 °C and 100 rpm until it was completely dissolved. After being transferred to a mold, it was irradiated under 405 nm ultraviolet light for five minutes to form a shape. The prepared hydrogel was immersed in 0.1 mol / L FeCl3 solution for 24 h. Example 3
[0033] At 25°C, 0.5 g of sodium carboxymethyl cellulose type I and 1.5 g of CCNF were weighed and dissolved in 20 mL of deionized water, and stirred at 25 °C and 100 rpm for 12 h until uniform and completely dissolved. 6 g of acrylamide, 15 mg of N,N'-methylenebisacrylamide crosslinker, 30 mg of I2959 photoinitiator, a small amount of catalyst tetramethylethylenediamine 20 μL, and 4 mL of single-walled carbon nanotube dispersion were taken, and stirred at 25 °C and 100 rpm until completely dissolved. After transferring to a mold, it was irradiated under 405 nm ultraviolet light for five minutes to form a mold. The prepared hydrogel was immersed in 0.1 mol / L FeCl3 solution for 24 h. Example 4
[0034] At 25°C, 0.5 g of sodium carboxymethyl cellulose type I and 1.75 g of CCNF were weighed and dissolved in 20 mL of deionized water. The mixture was stirred at 25 °C and 100 rpm for 12 h until it was evenly and completely dissolved. 6 g of acrylamide, 15 mg of N,N'-methylenebisacrylamide crosslinker, 30 mg of I2959 photoinitiator, 20 μL of a small amount of catalyst tetramethylethylenediamine and 4 mL of single-walled carbon nanotube dispersion were taken and stirred at 25 °C and 100 rpm until it was completely dissolved. After being transferred to a mold, it was irradiated under 405 nm ultraviolet light for five minutes to form a mold. The prepared hydrogel was immersed in 0.1 mol / L FeCl3 solution for 24 h. Example 5
[0035] At 25°C, 0.5 g of sodium carboxymethyl cellulose type I and 2.0 g of CCNF were weighed and dissolved in 20 mL of deionized water, and stirred at 25 °C and 100 rpm for 12 h until uniform and completely dissolved. 6 g of acrylamide, 15 mg of N,N'-methylenebisacrylamide crosslinker, 30 mg of I2959 photoinitiator, a small amount of catalyst tetramethylethylenediamine 20 μL, and 4 mL of single-walled carbon nanotube dispersion were taken, and stirred at 25 °C and 100 rpm until completely dissolved. After transferring to a mold, it was irradiated under 405 nm ultraviolet light for five minutes to form a mold. The prepared hydrogel was immersed in 0.1 mol / L FeCl3 solution for 24 h.
[0036] The hydrogels prepared in Examples 1 to 5 were subjected to compression performance tests, with hardness as an indicator.
[0037] Testing of hydrogel properties: The hydrogel was compressed to 65% deformation using a texture analyzer (TMS-Pro), and the hardness of the hydrogel was recorded.
[0038] The specific test results are shown in Table 2 Table 2 Results of the molding time test of the autocatalytic hydrogels prepared in Examples 1-5 Example CCNF addition amount Maximum tensile strain 1 1.0 g 238 % 2 1.25 g 282 % 3 1.5 g 297 % 4 1.75 g 263 % 5 2.0 g 242 % It can be seen from the above embodiments that the present invention provides a photocurable dual-network sensing hydrogel material and a preparation method thereof. The hydrogel has the best hardness at a CMC content of 0.5 g, and the maximum hardness at 60% deformation is 99.29714N. Adding 1.5 g CCNF has the best tensile effect, and the maximum tensile strain can reach 297%. The hydrogel enhanced by immersion in ferric chloride solution greatly improves its mechanical properties. The maximum hardness of the hydrogel immersed in 0.1 mol / L ferric chloride concentration reaches 446.13502 N, which is 349% higher than that of the hydrogel without ion enhancement, proving that ion enhancement has a significant effect. The photocurable dual-network hydrogel has an excellent mechanical property foundation.
[0039] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A photocurable dual network sensing hydrogel material and a preparation method thereof, characterized in that: The steps include: (1) Preparation of double network precursor solution: The cellulose ether derivative is stirred evenly until it is completely dissolved, and then carboxylated cellulose nanofibers (CCNF) and acrylamide are added and stirred evenly at a low speed to avoid generating bubbles until a double network precursor solution is formed; (2) Preparation of hydrogel: After the components in (1) are completely dissolved, add the photoinitiator I2959 and the cross-linking agent, add a small amount of catalyst, add the conductive carbon material, stir evenly and immediately transfer to the mold, and irradiate under ultraviolet light for 5-15 minutes until it is formed, then transfer to the metal ion solution for immersion to enhance the mechanical properties of the hydrogel.
2. The photocurable dual network sensing hydrogel material and the preparation method thereof according to claim 1, characterized in that: In the step (1), the mass fraction of the cellulose ether derivative added is 0.5wt%-2.5wt% relative to the water solvent, the mass fraction of the carboxylated cellulose nanofiber added is 5-10wt% relative to the water solvent, and the mass fraction of acrylamide added is 5wt%-25wt% relative to the water solvent. The stirring is carried out at 25°C-28°C, the rotation speed is 50-200 rpm, and the stirring time is 6-24 h.
3. The photocurable dual network sensing hydrogel material and the preparation method thereof according to claim 1, characterized in that: In the step (1), the cellulose ether derivative used is one of sodium carboxymethyl cellulose type I, hydroxyethyl cellulose, and hydroxypropyl cellulose.
4. The photocurable dual network sensing hydrogel material and the preparation method thereof according to claim 1, characterized in that: In the step (2), the mass fraction of the added cross-linking agent is 0.025wt% - 0.075wt% relative to the water solvent, the mass fraction of the added photoinitiator is 0.1wt% - 0.25wt% relative to the water solvent, the volume fraction of the added catalyst relative to the deionized water is 0.1%-0.5%, and the volume fraction of the added conductive carbon material relative to the water solvent is 5%-25%. Stirring is carried out at 25°C - 28°C, the rotation speed is 50 - 200 rpm, and the stirring time is 5min - 60min.
5. The photocurable dual network sensing hydrogel material and the preparation method thereof according to claim 1, characterized in that: In the step (2), the metal ion concentration is 0.1 mol / L-0.6 mol / L, the immersion is carried out at 25°C-28°C, and the immersion time is 6-24 h.
6. The photocurable dual network sensing hydrogel material and the preparation method thereof according to claim 1, characterized in that: In the step (2), the crosslinking agent used is one of N,N'-methylenebisacrylamide, glutaraldehyde, and N-hydroxymethylacrylamide, and the conductive carbon material used is at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes, graphite powder, and carbon nanofibers.
7. The photocurable dual network sensing hydrogel material and the preparation method thereof according to claim 1, characterized in that: In the step (2), the ultraviolet light wavelength used is 365-405 nm, the metal ion used is one of iron ion, zirconium ion, cerium ion and lead ion, and the irradiation time is 5-15 min.
8. A photocurable dual network sensing hydrogel material and a preparation method thereof, characterized in that: The hydrogel is synthesized by a double network sensing hydrogel prepared by the synthesis method described in any one of claims 1 to 7.
Citation Information
Patent Citations
Ion-covalent double-network hydrogel and preparation method thereof
CN105461945A
Preparation method of high-strength acrylamide-carboxymethylcellulose double-network structured hydrogel fire-fighting pad
CN109651625A
Preparation method and application of nanocellulose polymer optical composite hydrogel
CN112851972A
Printable double-network cross-linked polyacrylamide hydrogel electrolyte as well as preparation and application thereof
CN117134002A
Self-adhesion anti-freezing moisturizing multifunctional conductive hydrogel as well as preparation method and application thereof
CN117229530A